High-corrosion-resistance bimetal composite anchor chain and preparation method thereof

By using a bimetal composite structure of stainless steel cladding, NiCuP alloy intermediate layer and carbon steel base layer in the anchor chain, combined with laser etching and pre-alloying treatment, the problem of conventional anchor chains being easily corroded in the marine environment is solved, and an anchor chain structure with high corrosion resistance and strength is achieved.

CN119503076APending Publication Date: 2025-02-25RUNQIAO BIMETAL TECH XINJIANG CO LTD

Patent Information

Application Number
CN202411630980.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional anchor chains are susceptible to corrosion and wear in marine environments, resulting in a shortened service life and an increase in safety risks. Especially in deep-sea and extreme environments, the prior art is difficult to meet the requirements of anchor chains with high mechanical properties, corrosion resistance and fatigue resistance.

Method used

A high corrosion-resistant bimetallic composite anchor chain structure is adopted, including stainless steel cladding, NiCuP alloy intermediate layer and carbon steel base layer. A wave-shaped depression structure is formed through laser etching technology to enhance the metal contact area and bonding force, and close bonding between metals is achieved through pre-alloying and rolling processes.

Benefits of technology

It significantly improves the corrosion resistance of the anchor chain, reduces the degree of intergranular corrosion, and maintains a high-strength carbon steel base layer and a high-corrosion-resistant stainless steel cladding, extending the service life of the anchor chain and enhancing safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503076A_ABST
    Figure CN119503076A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anchor chain structures, and discloses a high-corrosion-resistance bimetal composite anchor chain and a preparation method thereof.According to the bimetal composite anchor chain, a stainless steel coating, an alloy middle layer and a carbon steel base layer are combined together in a hot rolling compounding mode, and the stainless steel coating and the alloy middle layer are in concave fit; the carbon steel base layer and the alloy middle layer are in concave fit. The alloy middle layer comprises Ni, Cu and P, and the content of Ni at the concave structure is far lower than that at the plane structure. The bimetallic composite anchor chain provided by the invention not only has high corrosion resistance of the stainless steel coating layer, but also can maintain high strength of the carbon steel base layer, carbon elements can be more effectively prevented from diffusing from carbon steel to stainless steel by the concave structure and distribution and content of Ni, Cu and P of the NiCuP alloy intermediate layer, and cathode protection can be performed on the stainless steel coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anchor chain structures, and in particular to a highly corrosion-resistant bimetallic composite anchor chain and a preparation method thereof. Background Art

[0002] Anchor chains are important equipment used to fix and stabilize ships or platforms in ships and marine engineering. Traditional anchor chains are usually made of a single metal material. Although these materials have high strength and durability, they are susceptible to corrosion and wear when used for a long time in the marine environment, resulting in a shortened service life and increased safety hazards. In recent years, with the increase in marine development activities, the performance requirements for anchor chains have become increasingly higher. Especially in deep sea and extreme environments, anchor chains need to have not only excellent mechanical properties, but also good corrosion resistance and fatigue resistance. The main alloying element in stainless steel is Cr (chromium). Only when the Cr content reaches a certain value, the steel has corrosion resistance. Carbon steel generally contains a large amount of carbon, a small amount of silicon, manganese, sulfur, and phosphorus. Generally, the higher the carbon content in carbon steel, the greater the hardness and strength, but the lower the plasticity.

[0003] At present, direct combination of carbon steel and stainless steel is prone to chemical corrosion and has poor long-term stability, so there are many deficiencies. The Chinese patent with publication number CN101085455A discloses a method for manufacturing a spiral composite steel pipe. In its patent document, it adopts internal welding and external welding to weld the stainless steel composite steel pipe. Such a welding method will inevitably cause a part of the carbon steel to penetrate into the stainless steel liquid when the stainless steel pipe is internally welded, so that the stainless steel pipe formed after welding has poor corrosion resistance, and the structural strength of the entire composite steel pipe is not high enough. The current solution is to add an intermediate layer between carbon steel and stainless steel to slow down the corrosion rate of carbon steel and stainless steel, but the current solution still cannot significantly reduce the corrosion rate of carbon steel and stainless steel, so there are many deficiencies. The utility model patent with authorization announcement number CN2196720Y discloses a stainless steel composite welded steel pipe, whose inner layer is a stainless steel pipe, the outer layer is a carbon steel pipe, and the middle is a high-temperature plastic fusion layer, and after being set, it is cold drawn or expanded to form a composite steel pipe. However, the bonding strength between the stainless steel pipe and the carbon steel pipe of the stainless steel composite steel pipe in this way is not high enough. In this regard, the present application provides a bimetallic composite anchor chain and a preparation method thereof to overcome the above problems. Summary of the invention

[0004] In view of the problem in the prior art that anchor chains made of a single metal are susceptible to corrosion and wear, the present application provides a highly corrosion-resistant bimetallic composite anchor chain and a preparation method thereof, which can significantly improve the corrosion resistance while maintaining the strength of the anchor chain.

[0005] In order to solve the above problems, the technical solutions adopted in this application are as follows:

[0006] On the one hand, the present application provides a highly corrosion-resistant bimetallic composite anchor chain, which includes a stainless steel coating, an alloy intermediate layer and a carbon steel base layer, wherein the stainless steel coating and the carbon steel base layer are combined together through the alloy intermediate layer, wherein a recessed fit is formed between the stainless steel coating and the alloy intermediate layer, and a recessed fit is formed between the alloy intermediate layer and the carbon steel base layer.

[0007] Furthermore, the alloy intermediate layer includes stainless steel elements, elements that reduce the melting point of stainless steel, and conductive elements.

[0008] Furthermore, the stainless steel element includes any one or more of Ni, Fe, Cr, Mo, Cu, Si, and Mn. Furthermore, the stainless steel element is Ni.

[0009] Further, the element that reduces the melting point of stainless steel includes P and / or B. Further, the element that reduces the melting point of stainless steel is P.

[0010] Furthermore, the conductive element includes any one or more of Ag, Cu, Au, Al, Zn, and Fe. Furthermore, the conductive element is Cu.

[0011] Furthermore, the content of Ni in different positions of the alloy intermediate layer is different, and the content of Ni located at the concave structure of the stainless steel cladding and the carbon steel base is higher than the content of Ni located at the planar structure of the stainless steel cladding and the carbon steel base.

[0012] Furthermore, the mass fraction of Ni in the alloy intermediate layer is 50%-90%, the mass fraction of Cu is 5%-40%, and the mass fraction of P is 5%-10%.

[0013] Furthermore, the depression includes a foundation pit shape, a wave shape or an island shape. Furthermore, the depression is a wave shape, and the wave shape design can greatly increase the actual contact area between the two contact surfaces. Due to the increase in the contact area, the wave shape matching can provide a stronger mechanical interlocking effect, thereby enhancing the bonding force between the components.

[0014] Furthermore, the alloy intermediate layer includes a first surface located on one side and a second surface opposite to the first surface, and the first surface and the second surface independently extend inward to form a depression or extend outward to form a protrusion.

[0015] Furthermore, the structure of the alloy intermediate layer is: Cu, P, Ni from the outside to the inside on both sides.

[0016] On the other hand, the present application also provides a method for preparing a highly corrosion-resistant bimetallic composite anchor chain, comprising:

[0017] A concave structure is formed on the surface of one side where the preset carbon steel base layer and the stainless steel cladding layer are close to each other;

[0018] An alloy intermediate layer is arranged between the carbon steel base layer and the stainless steel cladding. One side surface of the alloy intermediate layer forms a concave fit with the concave structure on the surface of the carbon steel base layer, and the other side surface of the alloy intermediate layer forms a concave fit with the concave structure on the surface of the stainless steel cladding layer.

[0019] Furthermore, the preparation method specifically comprises the following steps:

[0020] (1) Prepare carbon steel round bars and stainless steel pipes of appropriate sizes.

[0021] (2) Degrease and derust the surface of carbon steel round steel to remove oil, rust and other impurities on the surface. Clean the outer and inner surfaces of the stainless steel pipe to remove dust, grease and other contaminants. The cleaned stainless steel pipe should be smooth, without scratches and damage.

[0022] (3) Using laser etching technology, a wavy concave structure is formed on the surface of the carbon steel round bar and the inner side of the stainless steel tube. By adjusting parameters such as laser power, scanning speed and focal length, the depth and shape of the wavy concave structure are controlled to achieve the best bonding effect. The wavy concave structure formed on the surface of the carbon steel round bar and the inner side of the stainless steel tube can increase the contact area between the two metals and improve the bonding strength.

[0023] (4) The concave structures on the surface of carbon steel round steel and the inside of stainless steel pipe are identified through image recognition technology. Combined with machine vision and automated control systems, the concave structures can be automatically identified and located, thereby improving production efficiency and accuracy.

[0024] (5) Pre-alloying treatment: NiCuP alloy is plated on the surface of carbon steel round steel and the inner side of stainless steel pipe respectively. The thickness and uniformity of the coating are precisely controlled by controlling parameters such as electroplating time and current density. Too thick a coating may lead to a decrease in bonding strength, while too thin a coating may not provide adequate protection.

[0025] (6) The pre-alloyed carbon steel round bar in step (5) is placed into a pre-alloyed stainless steel tube to obtain a composite blank.

[0026] (7) After heating the composite billet of step (6), rolling and bonding are performed according to the rolling process so that the two metals are tightly bonded under high temperature and high pressure. During the rolling process, parameters such as rolling ratio, rolling temperature and rolling speed need to be controlled to ensure product quality. Then, the oxide layer is cleaned by sandblasting on the surface.

[0027] (8) The material obtained in step (7) is heated again, and after heating, it is braided into a ring shape, and the ring-shaped materials are connected to form an anchor chain structure.

[0028] Beneficial effects of this application:

[0029] (1) The present application provides a highly corrosion-resistant bimetallic composite anchor chain, in which the concave structure of the stainless steel coating and the carbon steel base layer can increase the thickness of the NiCuP alloy intermediate layer, thereby better preventing the diffusion of carbon elements from carbon steel to stainless steel and reducing the degree of intergranular corrosion.

[0030] (2) The application provides a highly corrosion-resistant bimetallic composite anchor chain, in which the NiCuP alloy distribution utilizes the combined effects of factors such as the diffusion barrier effect of the intermediate layer material, the advantages of the multilayer structure, the excellent performance of the amorphous metal film, and the good matching with the base material. These factors work together to make the NiCuP alloy an effective diffusion barrier material. Ni or its alloy as the intermediate layer can effectively slow down or prevent the diffusion of other metal elements. This distribution is more conducive to preventing the diffusion of carbon elements in carbon steel.

[0031] (3) The present application provides a highly corrosion-resistant bimetallic composite anchor chain that has both the high corrosion resistance of the stainless steel coating and the high strength of the carbon steel base layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of a cross section of a highly corrosion-resistant bimetallic composite anchor chain provided in Example 1 of the present application;

[0033] Among them, 1 is a stainless steel cladding, 2 is an alloy intermediate layer, and 3 is a carbon steel base layer.

[0034] Figure 2 The double ring dynamic potential reactivation curves of the stainless steel coating surfaces of different bimetallic composite anchor chains in the examples and comparative examples of the present application.

[0035] Figure 3 The potentiodynamic polarization curves of the stainless steel coating surfaces of different bimetallic composite anchor chains in the examples and comparative examples of the present application in a 3.5 wt. % NaCl solution.

[0036] Figure 4 This is a finished product picture of a highly corrosion-resistant bimetallic composite anchor chain provided in Example 1 of the present application. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0038] Before introducing the embodiments of the present application, the relevant terms involved in the embodiments of the present application are explained as follows:

[0039] High corrosion resistance: refers to the ability of a material to maintain its original performance and shape in harsh environments without chemical reactions or physical changes. The corrosion resistance of a material is directly related to the service life and safety of the equipment.

[0040] Stainless steel coating: is a stainless steel protective layer formed on the surface of metal or other materials through a special process to improve the corrosion resistance and mechanical properties of the material; stainless steel is an alloy steel whose main components include iron, chromium and nickel, among which the chromium content is usually above 10.5%, which is the key element that gives stainless steel corrosion resistance. In addition to these three main elements, stainless steel may also contain other elements such as carbon, manganese, silicon, phosphorus, sulfur, molybdenum, copper, nitrogen, titanium, aluminum, boron, cobalt, tantalum, tin, vanadium, tungsten, etc. The addition of these elements can further improve the performance of stainless steel.

[0041] Carbon steel base: Carbon steel base refers to the part of the composite material that serves as the basic structural layer and mainly provides strength and rigidity. Carbon steel is mainly composed of iron, carbon and other elements, with the carbon content ranging from 0.0218% to 2.11%, which determines its hardness and strength. In composite materials, such as carbon steel stainless steel composite plates, carbon steel is usually used as the base layer, while stainless steel is used as the cladding. This design allows the stainless steel to take on the protective role when the material is exposed to corrosive media or high temperature environments, while carbon steel is responsible for providing the necessary structural strength and rigidity. Due to the significant differences in chemical composition and physical properties between carbon steel and stainless steel, the same welding materials and processes cannot be used when welding such composite materials. The usual practice is to first use carbon steel welding materials to weld the carbon steel base layer, use transition welding materials when approaching the stainless steel layer, and finally use stainless steel welding materials to complete the welding of the cladding.

[0042] Alloy interlayer: Alloy interlayer is a special alloy usually composed of one or more elements and iron, mainly used in steel smelting. It uses a metal as the matrix and adds other elemental metals to it to solve the problems of these elements being easy to burn out at high temperatures, difficult to melt due to high melting points, or easy to segregate due to high density. Alloy interlayers usually have lower melting points and faster dissolution rates, which makes them easier to fuse with other metals at high temperatures. Alloy interlayers also have a strong ability to improve alloy properties, and can refine grains, perform modification treatments, and purify treatments.

[0043] Recessed fit: refers to a specific type of mechanical fit in which a raised portion of one part fits with a recessed portion of another part.

[0044] Laser etching technology: Laser etching technology is a high-precision material surface processing method. It irradiates the material surface with a high-energy laser beam and uses photothermal effect or photochemical reaction to etch patterns or text.

[0045] Image recognition technology: A key technology in the field of artificial intelligence that involves using computer systems to process, analyze and understand images to identify and classify various targets and objects in images.

[0046] Intergranular corrosion: It is a common corrosion phenomenon of metal materials. It mainly occurs at the grain boundaries of metals or alloys. This corrosion is caused by the difference in chemical composition, microstructure or stress state between the grain boundary area and the interior of the grain. Intergranular corrosion not only reduces the mechanical properties of the material, but may also cause material failure.

[0047] Melting point: The temperature at which the solid and liquid states of a pure substance are in equilibrium under a certain pressure.

[0048] Double-cycle dynamic potentiodynamic reactivation method: It is a technology that evaluates the intergranular corrosion sensitivity of a material by measuring its polarization behavior at a specific potential. This method is based on the principle of electrochemical kinetics and evaluates the intergranular corrosion tendency of a material by analyzing the current changes during anodic polarization and reactivation.

[0049] Potentiodynamic polarization curve test: The potentiodynamic polarization curve test determines the polarization curve of the sample by applying a certain current and measuring the change of the sample potential over time. This method is based on the principle of electrochemical reaction and evaluates the corrosion behavior of the sample under different environmental conditions by analyzing the shape and characteristics of the polarization curve.

[0050] Self-corrosion potential: The potential difference reached when a metal contacts a solution without an applied current. The self-corrosion potential reflects the degree of corrosion tendency of a metal in a specific solution and is a mixed potential of the anodic reaction and the cathodic reaction.

[0051] Self-corrosion current density: refers to the amount of current passing through a unit area. It is one of the important indicators for measuring the corrosion resistance of metals. The self-corrosion current density reflects the corrosion rate of metals in a specific solution, that is, the rate at which metal ions are transferred from the metal surface to the solution.

[0052] Pitting potential refers to the potential of a metal when its surface changes from a passivated state to an activated state in a specific solution. Pitting potential reflects the degree of corrosion tendency of a metal in a specific solution and is a mixed potential of anodic reaction and cathodic reaction.

[0053] An embodiment of the present application provides a highly corrosion-resistant bimetallic composite anchor chain, which includes a stainless steel coating, an alloy intermediate layer and a carbon steel base layer, wherein the stainless steel coating and the carbon steel base layer are combined together through the alloy intermediate layer, wherein a recessed fit is formed between the stainless steel coating and the alloy intermediate layer, and a recessed fit is formed between the alloy intermediate layer and the carbon steel base layer.

[0054] The embodiment of the present application provides a highly corrosion-resistant bimetallic composite anchor chain, in which the recessed structure of the stainless steel coating and the carbon steel base layer can increase the thickness of the alloy intermediate layer, thereby better preventing the diffusion of carbon elements from carbon steel to stainless steel and reducing the degree of intergranular corrosion.

[0055] In the present application, the alloy intermediate layer includes stainless steel elements, elements that reduce the melting point of stainless steel, and conductive elements.

[0056] In the present application, the above-mentioned stainless steel elements include any one or more of Ni, Fe, Cr, Mo, Cu, Si, and Mn. Ni can improve the crystal structure of stainless steel, increase the stability of austenite, improve toughness and plasticity, and make stainless steel have good mechanical properties even at low temperatures; at the same time, Ni can also enhance the resistance of stainless steel to some specific types of corrosion, such as stress corrosion cracking caused by chlorine; Cr is the key element that gives stainless steel stainlessness, it forms a dense oxide film in the steel, this film can effectively prevent further oxidation reactions, thereby improving the corrosion resistance of the material; Fe is the basic element of stainless steel and constitutes its main structure; stainless steel also contains other alloying elements, such as Mo, Mn, Si, etc., the addition of these trace elements can further enhance certain properties of stainless steel, such as high temperature resistance, processing performance or specific corrosion resistance.

[0057] In the present application, the above-mentioned elements for reducing the melting point of stainless steel include P and / or B. Among them, B is an effective grain refiner, which can significantly reduce the melting point of steel. Adding an appropriate amount of boron to stainless steel can improve the hot working properties of steel, while increasing its strength and hardness at high temperatures. Boron can also enhance the corrosion resistance of stainless steel, especially in a chloride ion environment; P is also one of the effective elements for reducing the melting point of steel. It can expand the austenite phase region of steel, reduce the melting point of steel, and improve its creep resistance. Excessive phosphorus content may increase the brittleness of steel, and its addition amount needs to be controlled.

[0058] In the present application, the above-mentioned conductive elements include any one or more of Ag, Cu, Au, Al, Zn, and Fe. Among them, Ag is the material with the best electrical and thermal conductivity among all metals. It has high electrical conductivity and is often used in high-precision electronic equipment and high-end decorations. Due to its high cost, Ag is usually not used in large quantities as the main conductive material; Cu's conductivity is second only to Ag, and its cost is relatively low, so it is widely used in industry as the main material for wires, cables and other electrical equipment; Although Au is not as conductive as silver and copper, it is often used in connection points and decorative plating of high-end electronic products due to its excellent corrosion resistance and beautiful appearance; Al's conductivity is lower than Ag, Cu and Au, but due to its light weight and cost-effectiveness, aluminum is still a popular choice in certain specific applications, such as power transmission lines and certain types of radiators; Zn's conductivity is not as good as the above-mentioned metals, but it is widely used in alloy manufacturing, especially in the production of galvanized steel sheets to improve the corrosion resistance of materials; Iron's conductivity is the weakest among these metals, but due to its abundant reserves and low cost, iron and its alloys are widely used in construction, machinery and automotive industries.

[0059] In the embodiment of the present application, the stainless steel element is Ni, the stainless steel melting point element is P, and the conductive element is Cu, wherein the mass fraction of Ni is 50%-90%, the mass fraction of Cu is 5%-40%, and the mass fraction of P is 5%-10%.

[0060] In the present application, the recessed fit includes a pit shape, a wave shape or an island shape.

[0061] The recessed fit described in the embodiment of the present application is wavy in shape. The wavy design can greatly increase the actual contact area between the two contact surfaces. Due to the increase in the contact area, the wavy fit can provide a stronger mechanical interlocking effect, thereby enhancing the bonding force between the components.

[0062] In the present application, the alloy intermediate layer includes a first surface located on one side and a second surface opposite to the first surface, and the first surface and the second surface independently extend inward to form a depression or extend outward to form a protrusion.

[0063] In the embodiment of the present application, the structure of the alloy intermediate layer is: Cu, P, Ni from the outside to the inside on both sides.

[0064] Correspondingly, the present application also provides a method for preparing the above-mentioned bimetallic anchor chain, comprising: forming a recessed structure on the surface of one side where a preset carbon steel base layer and a stainless steel coating are close to each other; configuring an alloy intermediate layer between the carbon steel base layer and the stainless steel coating, wherein one side surface of the alloy intermediate layer forms a recessed fit with the recessed structure on the surface of the carbon steel base layer, and the other side surface of the alloy intermediate layer forms a recessed fit with the recessed structure on the surface of the stainless steel coating.

[0065] In the embodiment of the present application, the specific steps of the preparation method include:

[0066] S01. Prepare carbon steel round steel and stainless steel pipe;

[0067] S02. Degrease and rust the surface of carbon steel round steel, and clean the outer surface and inner side of stainless steel pipe;

[0068] S03. Using laser etching technology to form a wavy concave structure on the outer surface of the carbon steel round steel and the inner side of the stainless steel tube;

[0069] S04. Identify the concave structures on the surface of carbon steel round steel and the inside of stainless steel pipe through image recognition technology;

[0070] S05. Pre-alloying treatment: NiCuP alloy is plated on the surface of carbon steel round steel and the inner side of stainless steel pipe respectively;

[0071] S06. The pre-alloyed carbon steel round steel in step S05 is loaded into the pre-alloyed stainless steel tube to obtain a composite billet;

[0072] S07. After heating the composite billet of step S06, rolling and compounding are performed according to the rolling process, and the oxide layer is cleaned by sandblasting on the surface;

[0073] S08. The material obtained in step S07 is heated again, and after heating, it is braided into a ring shape, and the ring-shaped material is connected to form an anchor chain structure.

[0074] In the above step S03, the laser etching technology forms a precise wavy pattern on the surface of the material through a high-energy laser beam, enhances the mechanical interlocking effect of the material, and the wavy concave structure formed helps to improve the bonding force between the two metals and make the composite more solid. During the laser etching process, the laser beam hits the surface of the component, and the surface of the component absorbs the beam energy and converts it into heat. In addition, it also converts most of the reflected beam energy into heat, and the material absorbs the energy to melt and expand its microscopic surface. After the beam energy is converted into heat, the temperature of the material rises. Due to the high heat, the ductility of the surface of the component increases, causing its shape to change. The surface of the material will undergo different changes after melting and cooling for a short time, forming permanent high-quality marks on the surface of the material.

[0075] The laser etching technology adjusts the laser power to 250W, the scanning speed to 120mm / s, the laser pulse energy to 50mJ, the laser beam diameter to 65μm, and the scanning mode to linear scanning, thereby controlling the depth and shape of the wavy concave structure to achieve the best bonding effect.

[0076] In the above step S04, the image recognition technology includes the following key components: industrial CCD camera: used to capture the image of the steel plate surface; LED lighting system: irradiates the steel plate surface in a specific direction to help highlight the surface features; image acquisition card: inputs the image signal captured by the camera into the computer; image processing computer system: performs image preprocessing, such as binarization processing, and extracts geometric feature parameters; data statistics and management system: used to manage and analyze the detection results.

[0077] The image recognition technology is based on the study of the reflection properties of light on the surfaces of different materials. For carbon steel and stainless steel, due to their different physical properties, the reflection properties of light are also different. Taking advantage of this property, different detection methods can be used to identify the surface depression structure: Bright field method: suitable for detecting two-dimensional and three-dimensional defects on the surface of ordinary carbon steel. In this method, the light source directly shines on the surface of the steel plate, and the camera captures the reflected light to form a clear image, which is convenient for subsequent image processing and analysis; Dark field method: suitable for detecting three-dimensional defects on the surface of stainless steel. In this method, the light source shines at a certain angle so that only scattered light is captured by the camera, thereby highlighting the depressions and other minor defects on the surface.

[0078] In the above step S05, the pre-alloying treatment refers to coating a layer of NiCuP alloy on the surface of the material to improve its corrosion resistance and wear resistance.

[0079] In the above step S07, the material is softened by high temperature heating, and then a rolling process is used to achieve close bonding between metals. Sandblasting technology is used to remove the oxide layer on the surface to improve the appearance quality and durability of the product.

[0080] In the above step S07, the rolling ratio, rolling temperature and rolling speed need to be controlled during the rolling process, with the rolling ratio being 1.2 and the rolling speed being 20 m / min, to ensure product quality.

[0081] In the above step S08, the material is heated again to maintain its plasticity, and then it is woven into a ring structure, and the ring materials are connected by welding or other connection methods to finally form a complete anchor chain structure.

[0082] In the above step S08, the heating temperature is 900°C, the heating time is adjusted according to the material thickness and equipment capacity, usually 15 minutes, the material is heated and woven into a ring, and the ring-shaped material is connected to form an anchor chain structure.

[0083] Example 1

[0084] This embodiment provides a highly corrosion-resistant bimetallic composite anchor chain, such as Figure 1 As shown, it includes a stainless steel cladding 1, a NiCuP alloy intermediate layer 2 and a carbon steel base layer 3, wherein the stainless steel cladding 1 and the carbon steel base layer 3 are combined together through the NiCuP alloy intermediate layer 2, wherein a concave fit is formed between the stainless steel cladding 1 and the NiCuP alloy intermediate layer 2, and a concave fit is formed between the NiCuP alloy intermediate layer 2 and the carbon steel base layer 3. The mass fractions of the elements in the NiCuP alloy intermediate layer 2 are 60%, 30% and 10% respectively.

[0085] The specific preparation method of the bimetallic composite anchor chain comprises the following steps:

[0086] (1) Prepare carbon steel round bars and stainless steel pipes of appropriate sizes.

[0087] (2) Degrease and rust the surface of carbon steel round steel to remove surface oil, rust and other impurities. Clean the surface and inside of the stainless steel pipe to remove surface dust, grease and other contaminants. The surface of the stainless steel pipe after cleaning should be smooth, without scratches and damage.

[0088] (3) Using laser etching technology, a wavy concave structure is formed on the surface of the carbon steel round steel and the inner side of the stainless steel tube. The laser power is adjusted to 250W, the scanning speed is 120mm / s, the laser pulse energy is 50mJ, the laser beam diameter is 65μm, and the scanning mode is linear scanning. The depth and shape of the wavy concave structure are controlled to achieve the best bonding effect. The wavy concave structure formed on carbon steel and stainless steel can increase the contact area between the two metals and improve the bonding strength.

[0089] (4) The concave structures on the outer surface of carbon steel and the inner surface of stainless steel are identified through image recognition technology. Combined with machine vision and automated control systems, the concave structures can be automatically identified and located, thereby improving production efficiency and accuracy.

[0090] (5) Pre-alloying treatment: NiCuP alloy is plated on the surface of carbon steel round steel and the inner side of stainless steel tube respectively. The NiCuP alloy is electroplated at a current density of 30Amin / dm 2The electrolyte temperature was 35°C and the pH value was 4. The composition and content of the electroplating solution for NiCuP alloy were NiSO4·6H2O, CuSO4·5H2O, NaH2PO2·H2O, and composite additives, with contents of 30g / L, 40g / L, 20g / L, and 40g / L, respectively, to obtain an alloy coating with a thickness of 0.5mm. The thickness and uniformity of the coating can be precisely controlled by controlling parameters such as electroplating time and current density. Too thick a coating may lead to a decrease in bonding strength, while too thin a coating may not provide adequate protection.

[0091] (6) The pre-alloyed carbon steel round bar in step (5) is placed into a pre-alloyed stainless steel tube to obtain a composite blank.

[0092] (7) The composite billet of step (6) is heated at a heating temperature of 900°C-1100°C, and rolled and composited according to a rolling process to allow the two metals to be tightly bonded under high temperature and high pressure. The rolling ratio, rolling temperature and rolling speed need to be controlled during the rolling process. The rolling ratio is 1.2 and the rolling speed is 20 m / min to ensure product quality. The oxide layer is then cleaned by sandblasting on the surface to ensure that the two metals are tightly bonded under high temperature and high pressure.

[0093] (8) The material obtained in step (7) is heated again, the heating temperature is 900°C, the heating time is adjusted according to the material thickness and equipment capacity, usually 15 minutes, the material is heated and woven into a ring shape, and the ring-shaped materials are connected to form an anchor chain structure. The finished product is shown in the figure. Figure 4 The SEM image of its cross section is shown in Figure 1 shown.

[0094] The bimetallic composite anchor chain produced according to the above preparation method can not only have the high corrosion resistance of the stainless steel coating, but also maintain the high strength of the carbon steel base layer and is not prone to intergranular corrosion.

[0095] Comparative Example 1

[0096] This embodiment provides a bimetallic composite anchor chain, which is different from the embodiment 1 in that the middle layer is NiP alloy, and the mass fractions of the elements in the NiP alloy middle layer are 90% and 10% respectively.

[0097] The specific preparation method of the bimetallic composite anchor chain comprises the following steps:

[0098] (1) Prepare carbon steel round bars and stainless steel pipes of appropriate sizes.

[0099] (2) Degrease and derust the surface of carbon steel round steel to remove surface oil, rust and other impurities. Clean the surface and inside of the stainless steel pipe to remove surface dust, grease and other contaminants. The surface of the stainless steel pipe after cleaning should be smooth, without scratches and damage.

[0100] (3) Using laser etching technology, a wavy concave structure is formed on the surface of the carbon steel round steel and the inner side of the stainless steel tube. The laser power is adjusted to 250W, the scanning speed is 120mm / s, the laser pulse energy is 50mJ, the laser beam diameter is 65μm, and the scanning mode is linear scanning. The depth and shape of the wavy concave structure are controlled to achieve the best bonding effect. The wavy concave structure formed on carbon steel and stainless steel can increase the contact area between the two metals and improve the bonding strength.

[0101] (4) The concave structures on the surface of carbon steel and the inside of stainless steel are identified through image recognition technology. Combined with machine vision and automated control systems, the concave structures can be automatically identified and located, thereby improving production efficiency and accuracy.

[0102] (5) Pre-alloying treatment: NiP alloy is plated on the surface of carbon steel round steel and the inner side of stainless steel tube respectively. The NiP alloy is electroplated at a current density of 30Amin / dm 2 The electrolyte temperature was 35°C and the pH value was 4. The composition and content of the electroplating solution for NiP alloy electroplating were NiSO4·6H2O, CuSO4·5H2O, NaH2PO2·H2O, and composite additives, with contents of 30g / L, 40g / L, 20g / L, and 40g / L, respectively, to obtain an alloy coating with a thickness of 0.5mm. The thickness and uniformity of the coating can be precisely controlled by controlling parameters such as electroplating time and current density. Too thick a coating may lead to a decrease in bonding strength, while too thin a coating may not provide adequate protection.

[0103] (6) The pre-alloyed carbon steel round bar in step (5) is placed into a pre-alloyed stainless steel tube to obtain a composite blank.

[0104] (7) After heating the composite billet of step (6), rolling and compounding are carried out according to the rolling process to make the two metals tightly bonded under high temperature and high pressure. The rolling ratio, rolling temperature and rolling speed need to be controlled during the rolling process. The rolling ratio is 1.2 and the rolling speed is 20 m / min to ensure the product quality. Then, the oxide layer is cleaned by sandblasting on the surface.

[0105] (8) The material obtained in step (7) is heated again, the heating temperature is 900° C., the heating time is adjusted according to the material thickness and equipment capacity, usually 15 minutes, the material is heated and woven into a ring shape, and the ring-shaped material is connected to form an anchor chain structure.

[0106] Comparative Example 2

[0107] This embodiment provides a bimetallic composite anchor chain, which is different from the embodiment 1 in that the inner surface of the stainless steel coating and the outer surface of the carbon steel base layer have no wavy concave structures.

[0108] The specific preparation method of the bimetallic composite anchor chain comprises the following steps:

[0109] (1) Prepare carbon steel round bars and stainless steel pipes of appropriate sizes.

[0110] (2) Degrease and rust the surface of carbon steel round steel to remove surface oil, rust and other impurities. Clean the surface and inside of the stainless steel pipe to remove surface dust, grease and other contaminants. The surface of the stainless steel pipe after cleaning should be smooth, without scratches and damage.

[0111] (3) Pre-alloying treatment: NiCuP alloy is plated on the surface of carbon steel round steel and the inner side of stainless steel tube respectively. The NiCuP alloy is electroplated at a current density of 30Amin / dm 2 The electrolyte temperature was 35°C and the pH value was 4. The composition and content of the electroplating solution for NiCuP alloy were NiSO4·6H2O, CuSO4·5H2O, NaH2PO2·H2O, and composite additives, with contents of 30g / L, 40g / L, 20g / L, and 40g / L, respectively, to obtain an alloy coating with a thickness of 0.5mm. The thickness and uniformity of the coating can be precisely controlled by controlling parameters such as electroplating time and current density. Too thick a coating may lead to a decrease in bonding strength, while too thin a coating may not provide adequate protection.

[0112] (4) The pre-alloyed carbon steel round bar in step (3) is placed into a pre-alloyed stainless steel tube to obtain a composite blank.

[0113] (5) After heating the composite billet of step (4), rolling and compounding are carried out according to the rolling process, so that the two metals are tightly combined under high temperature and high pressure. The rolling ratio, rolling temperature and rolling speed need to be controlled during the rolling process. The rolling ratio is 1.2 and the rolling speed is 20 m / min to ensure the product quality. Then, the oxide layer is cleaned by sandblasting on the surface.

[0114] (6) The material obtained in step (5) is heated again, the heating temperature is 900°C, the heating time is adjusted according to the material thickness and equipment capacity, usually 15 minutes, and the material is braided into a ring after heating, and the ring-shaped material is connected to form an anchor chain structure. The material is braided into a ring after heating, and the ring-shaped material is connected to form an anchor chain structure.

[0115] Performance Test:

[0116] 1. Double-ring potentiodynamic reactivation method

[0117] According to ASTMG108-94 (2015), the double-loop dynamic potential reactivation method (DL-EPR) test is carried out. The DL-EPR experiment includes two processes: activation and reactivation: the maximum current formed during the scanning from the activation potential of the material to the passivation potential is recorded as the activation current peak Ia; the reactivation current peak generated during the reverse scanning from the passivation potential of the material to the activation potential at the same rate is recorded as Ir. The intergranular sensitization degree DOS is obtained by calculating the value of Ir / Ia to evaluate the intergranular corrosion sensitization degree of the sample. The larger the DOS value, the higher the intergranular corrosion sensitivity of the material.

[0118] The intergranular corrosion test solution selected was 0.5mol / L H2SO4+0.01moI / L KSCN, and the scanning rate was 1.5mV / s. The sample was polarized from the open circuit potential. When the potential reached +0.3V, the scanning direction was reversed. At the same scanning rate (1.5mV / s), the scan was returned to the open circuit potential. The sensitization degree of intergranular corrosion (IGC) of the sample was evaluated by the Ir / Ia ratio.

[0119] Figure 2 DL-EPR curves of different samples. The electrochemical parameters obtained from the curves are summarized in Table 1. The DOS value of the composite anchor chain in Example 1 is 0.25%. Since the NiCuP alloy intermediate layer between the carbon steel base and the stainless steel coating can block the diffusion of carbon elements from the carbon steel base to the stainless steel coating, this shows that the stainless steel coating surface of the bimetallic composite anchor chain in Example 1 has good intergranular corrosion resistance.

[0120] Table 1 Electrochemical parameters in DL-EPR curves of stainless steel coatings on different samples

[0121]

[0122] 2. Potentiodynamic polarization curve test

[0123] The potentiodynamic polarization curve test determines the polarization curve of the sample by applying a certain current and measuring the change of the sample potential over time. This method is based on the principle of electrochemical reaction and evaluates the corrosion behavior of the sample under different environmental conditions by analyzing the shape and characteristics of the polarization curve.

[0124] According to ASTM G64-86 (2018), the experimental solution was selected as 3.5 wt.% NaCl solution, the scanning range was -300 mV to 500 mV (vs OCP), and the scanning rate was 1 mV / s.

[0125] Figure 3Table 2 shows the potentiodynamic polarization curves of the stainless steel coating surfaces of different samples in 3.5wt.% NaCl solution. The electrochemical parameters obtained according to the potentiodynamic polarization curves are listed in Table 2, mainly including corrosion electrochemical parameters such as self-corrosion potential (Ecorr), self-corrosion current density (Icorr) and pitting potential (Epit). The results show that the bimetallic composite anchor chain of Example 1 has a higher self-corrosion potential (-0.104V) and a lower self-corrosion current density (8.6×10 -8 A / cm 2 ), this is because there is almost no carbide precipitation on the surface of the bimetallic composite anchor chain coating of Example 1, and it has better resistance to pitting corrosion.

[0126] Table 2 Electrochemical parameters of stainless steel coating surfaces of different samples in 3.5wt.% NaCl solution

[0127]

[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly corrosion-resistant bimetallic composite anchor chain, characterized in that: The anchor chain comprises a stainless steel coating, an alloy intermediate layer and a carbon steel base layer, wherein the stainless steel coating and the carbon steel base layer are combined together through the alloy intermediate layer, wherein a concave fit is formed between the stainless steel coating and the alloy intermediate layer, and a concave fit is formed between the alloy intermediate layer and the carbon steel base layer.

2. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The alloy intermediate layer includes stainless steel elements, elements that reduce the melting point of stainless steel, and conductive elements.

3. A highly corrosion-resistant bimetallic composite anchor chain according to claim 2, characterized in that: The stainless steel elements include any one or more of Ni, Fe, Cr, Mo, Cu, Si, and Mn; the elements for reducing the melting point of stainless steel include P and / or B; and the conductive elements include any one or more of Ag, Cu, Au, Al, Zn, and Fe.

4. A highly corrosion-resistant bimetallic composite anchor chain according to claim 3, characterized in that: The stainless steel element is Ni; the element for reducing the melting point of stainless steel is P; and the conductive element is Cu.

5. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The Ni content at the concave structures of the stainless steel cladding and the carbon steel base layer is lower than the Ni content at the planar structures of the stainless steel cladding and the carbon steel base layer.

6. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The mass fraction of Ni in the alloy intermediate layer is 50%-90%, the mass fraction of Cu is 5%-40%, and the mass fraction of P is 5%-10%.

7. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The depression includes a foundation pit shape, a wave shape or an island shape.

8. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The alloy intermediate layer includes a first surface located on one side and a second surface opposite to the first surface, and the first surface and the second surface are independently extended inward to form a depression or extended outward to form a protrusion.

9. A highly corrosion-resistant bimetallic composite anchor chain according to claim 1, characterized in that: The element distribution of the alloy intermediate layer is Cu, P and Ni distributed in sequence along the direction from the outer side to the inner side of the alloy intermediate layer.

10. The method for preparing a highly corrosion-resistant bimetallic composite anchor chain according to any one of claims 1 to 9, characterized in that: The following steps are involved: A concave structure is formed on the surface of one side where the preset carbon steel base layer and the stainless steel cladding layer are close to each other; An alloy intermediate layer is arranged between the carbon steel base layer and the stainless steel cladding. One side surface of the alloy intermediate layer forms a concave fit with the concave structure on the surface of the carbon steel base layer, and the other side surface of the alloy intermediate layer forms a concave fit with the concave structure on the surface of the stainless steel cladding layer.

Citation Information

Patent Citations

  • Method for Manufacturing helix composite steel tube

    CN101085455A

  • Stain-less steel composite steel-pipe

    CN2196720Y

Cited By

  • Manufacturing method of stainless steel and carbon steel bimetal composite reinforcing steel bar

    CN120532891A